Antibacterial, antioxidant and antihypertensive properties of polyphenols from argentinean red wines varieties - María J Rodríguez-Vaquero; Claudia V Vallejo; Pedro A Aredes-Fernández (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2020)
The aims of this study were to determine the phenolic profile of three Argentinean wine varieties and their antioxidant, antihypertensive and antibacterial activities. Gallic acid, quercetin and rutin were the principal phenolic compounds identified in wines. All wines possess a high antihypertensive and antioxidant activities. Among 3 wines, merlot and malbec possess the higher ferric reducing power and DPPH and ABTS radical scavenging activity. Lower ferric reduced power and radical scavenging values were found in clarified wines. High correlation coefficients were found between phenolic content and antioxidant and antihypertensive capacities, confirming that phenolic compounds are likely the responsible for these activities in wines. The inhibition of biofilm formation and MIC and MBC values of wines polyphenols against E. coli, Pseudomonas aeruginosa, Staphylococcus aureus and L. monocytogenes was demonstrated. The higher antibacterial, antioxidant and ACEI activities of merlot and malbec wines compared with cabernet sauvignon could be related to the higher concentration of individual phenolic compounds, such as quercetin, rutin, kaempferol, caffeic acid and gallic acids in malbec and merlot wines.